Richard Schaukal in Netzwerken und Feldern der literarischen Moderne - Mitterer, Cornelius (Studien und Texte zur Sozialgeschichte der Literatur, 2020)
Richard Schaukal was in contact with some of literary modernism's most important protagonists. In his early creative years, he stylized himself as an independent, isolated poet. After World War I, Schaukal became increasingly visible as a cultural critic, using his letters, essays, and literary works to take a stand against the new realities. His biography offers insights into the aesthetic, social, and political developments of his time.